2003
DOI: 10.1007/s10162-002-3030-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Modelling of the Middle-Ear Ossicular Chain Using a Commercial High-Resolution X-Ray CT Scanner

Abstract: The quantitative measurement of the three-dimensional (3-D) anatomy of the ear is of great importance in the making of teaching models and the design of mathematical models of parts of the ear, and also for the interpretation and presentation of experimental results. This article describes how we used virtual sections from a commercial high-resolution X-ray computed tomography (CT) scanner to make realistic 3-D anatomical models for various applications in our middle-ear research. The important problem of regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…To formulate an accurate biomechanical model, individual anatomy may be important, which requires a fast and non-destructive method. This work shows that micro-CT imaging, which is known to be a suitable method for high-density tissue such as the ossicles and surrounding bone (Decraemer et al 2003;Lane et al 2004;Sim et al 2006;Puria et al 2007a), can also be used to image the soft tissues of the malleus-incus complex (Figs. 3 and 4).…”
Section: Introductionmentioning
confidence: 89%
“…To formulate an accurate biomechanical model, individual anatomy may be important, which requires a fast and non-destructive method. This work shows that micro-CT imaging, which is known to be a suitable method for high-density tissue such as the ossicles and surrounding bone (Decraemer et al 2003;Lane et al 2004;Sim et al 2006;Puria et al 2007a), can also be used to image the soft tissues of the malleus-incus complex (Figs. 3 and 4).…”
Section: Introductionmentioning
confidence: 89%
“…In previous CT-based studies of the ME, the following model resolutions were reported: 5.5 μm on gerbil (Elkhouri et al 2006), 6 μm on human (Hagr et al 2004), 10 μm on cat (Decraemer et al 2003), and 10 μm on human (Vogel 1999). Though these numbers are comparable to our isometric 8.5-μm voxel size for μCT on gerbil bone, our data and models are of much higher quality than those shown in previous work.…”
Section: Resolutionmentioning
confidence: 99%
“…Morphometric and volumetric characteristics of the parts of the human body are of great importance in the designing and manufacturing of their anatomical models and also in the interpretation and presentation of experimental results [16]. These models enable students, researchers and surgeons to better understand complex structures and facilitate diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%